Clinical and haematological characteristics of 38 individuals with Hb G‐Makassar in Malaysia - Ezalia Esa; Ahmad Sabry Mohamad; Roszymah Hamzah; Faidatul Syazlin Abdul Hamid; Nur Aisyah Aziz; Veena Sevaratnam; Jameela Sathar; Guo Chen; Norafiza Mohd Yasin (eJHaem, 2023)
Abstract Haemoglobin (Hb) G‐Makassar is a rare Hb variant. It presents a diagnostic challenge as it imitates sickle Hb (Hb S) in standard electrophoresis and high‐performance liquid chromatography assays requiring DNA analysis to confirm diagnosis. Both have point mutations in codon 6, exon 1 in the β‐globin (HBB) gene with different pathogenicities. This study describes the clinical phenotype, haematology and genotype of Hb G‐Makassar. Clinical and laboratory data of 38 cases of Hb G‐Makassar over 8 years were analysed. Hb G‐Makassar was confirmed by a direct sequencing of HBB gene and co‐inheritance of α‐thalassaemia determined through multiplex gap‐PCR and multiplex Amplification Refractory Mutation System polymerase chain reaction. All cases were Malays, predominantly from Terengganu (n = 20, 52.6%). There were 14 (36.8%) males and 24 (63.2%) females with median age of 25 years. Majority (n = 33, 86.8%) had features of thalassaemia trait with mean ± SD for Hb, mean cell volume (MCV) and mean cell haemoglobin (MCH) as 13.21 g/dL ± 1.69, 73.06 ± 4.48 fL and 24.71 ± 1.82 pg, respectively. None had evidence of haemolysis or thromboembolic complications. Six genotypes were identified; ßG‐Makassar/ß,αα/αα (n = 19, 50.0%), ßG‐Makassar/ßE,αα/αα (n = 4, 10.5%), ßG‐Makassar/ßNewYork,αα/αα (n = 1, 2.6%), ßG‐Makassar/ß,αα/‐α (n = 11, 28.9%), ßG‐Makassar/ß,αα/αAdanaα (n = 2, 5.3%) and ßG‐Makassar/ß,αα/–SEA (n = 1, 2.6%). The ßG‐Makassar/ß,αα/αα showed that features of thalassaemia trait with mean ± SD for Hb, MCV and MCH were 13.74 g/dL ± 2.40, 76.18 ± 6.02 fL and 25.79 ± 2.41 pg, respectively. This is the largest study reporting a significant number of Hb G‐Makassar in Malaysia. Although the mutation is similar to Hb S, the phenotype is benign.